2022
DOI: 10.1021/acscatal.1c05329
|View full text |Cite
|
Sign up to set email alerts
|

Defunctionalization of sp3 C–Heteroatom and sp3 C–C Bonds Enabled by Photoexcited Triplet Ketone Catalysts

Abstract: A general strategy for enabling a light-induced defunctionalization of sp 3 C−heteroatom and sp 3 C−C bonds with triplet ketone catalysts and bipyridine additives is disclosed. This protocol is characterized by its broad scope without recourse to transition metal catalysts or stoichiometric exogeneous reductants, thus offering a complementary technique for activating σ sp 3 C− C(heteroatom) bonds. Preliminary mechanistic studies suggest that the presence of 2,2′-bipyridines improves the lifetime of ketyl radic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 83 publications
0
13
0
Order By: Relevance
“…We started our investigations by studying the asymmetric C­(sp 3 )–H arylation of tetrahydrofuran 1 with ethyl 4-bromobenzoate 2 (Table ). Extensive evaluation of the reaction parameters identified that the combination of NiCl 2 ·DME, the chiral PHOX ligand L1 , Na 2 CO 3 , and the diaryl ketone PC1 as a photo-HAT catalyst , under irradiation with 10 W light-emitting diodes (LEDs) at −5 °C provided the desired product 3 in 75% yield and 90% e.e. (entry 1, condition A).…”
Section: Resultsmentioning
confidence: 99%
“…We started our investigations by studying the asymmetric C­(sp 3 )–H arylation of tetrahydrofuran 1 with ethyl 4-bromobenzoate 2 (Table ). Extensive evaluation of the reaction parameters identified that the combination of NiCl 2 ·DME, the chiral PHOX ligand L1 , Na 2 CO 3 , and the diaryl ketone PC1 as a photo-HAT catalyst , under irradiation with 10 W light-emitting diodes (LEDs) at −5 °C provided the desired product 3 in 75% yield and 90% e.e. (entry 1, condition A).…”
Section: Resultsmentioning
confidence: 99%
“…While significant progress has been made with sp 3 C–O electrophiles bearing electron-withdrawing groups adjacent to the oxygen atom, the sp 3 C–O functionalization of unactivated alkyl ethers arguably the simplest derivatives in the alcohol seriesstill remains a challenging endeavor in both two- and one-electron manifolds (Scheme ). This is probably attributed to (a) the lower tendency of alkyl ether residues to formally act as leaving groups, (b) the remarkably high activation barrier required for effecting alkyl sp 3 C–O cleavage (∼93 kcal·mol –1 ), and (c) inevitable site-selectivity issues arising from the functionalization at both alkyl sp 3 C–O sites.…”
mentioning
confidence: 99%
“…Therefore, we integrated these distinctive properties into one to further boost the photoredox efficiency and photostability in the resulting materials by creating a 2D COF with well-separated aryl-ketone units and a tunable pore environment. However, carbonyl-containing redox moieties have mainly been restricted to benzophenone derivatives. ,, Truxenones, which are composed of one central benzene ring fused by fluorenones, can undergo reversible multiple redox reactions, thus providing a higher capability in PET reactions. Additionally, truxenones with high symmetry and planarity may be used as novel building blocks in COF materials, and their potential in PET reactions remains largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…However, carbonyl-containing redox moieties have mainly been restricted to benzophenone derivatives. 24,29,30 Truxenones, which are composed of one central benzene ring fused by fluorenones, can undergo reversible multiple redox reactions, thus providing a higher capability in PET reactions. Additionally, truxenones with high symmetry and planarity may be used as novel building blocks in COF materials, 68 and their potential in PET reactions remains largely unexplored.…”
Section: ■ Introductionmentioning
confidence: 99%